Building Sharia Accounting Students Ethical Perceptions: Effects Of Ethical Content, Equity Sensitivity, and Locus of Control - Susanto, Trika; Aisyiah, Helti Nur (Indonesian Journal of Islamic Business and Economics (IJIBE), 2023)
This research aims to obtain empirical evidence about the effect of professional ethical content, equity sensitivity, and locus of control on the ethical perceptions of Sharia accounting students regarding unethical actions taken by accountants. The population in this research is comprised of Sharia accounting students at the IAIN Surakarta Faculty of Economics and Islamic Business, with a total sample size of 171 students. Samples were selected using the Slovin formula. The primary data sources used in this research were obtained through questionnaire distribution. The data analysis method used in this study is multiple regression analysis. The results of this research indicated that ethical content and equity sensitivity did not affect the ethical perception of Sharia accounting students regarding unethical actions taken by accountants. In contrast, the locus of control affected the ethical perceptions of Sharia accounting students regarding unethical actions taken by accountants. The results of this study are expected to contribute to the world of education, especially accounting education, in an effort to prepare prospective accountants to behave ethically.